Navigating and negotiating borders: Western pre-service teachers' experiences of teaching science in a non-western setting. (June 2019) - Fitzgerald, Angela
Abstract: The subculture of science has 'borders' that many find difficult to negotiate. These borders become more complex the further understandings of science are from traditional western perspectives. This paper examines the experiences of two western pre-service teachers' teaching science in a non-western context –the Cook Islands– using data gathered through interviews and learning logs. The lens of 'border crossing' has been used to make sense of these teachers' learning to teach experiences as it provides insights into the ways in which the participants negotiated such crossings over time. This research highlights the importance of recognising the positive interactions and potential for diverse experiences within a cultural context. Highlights: Confirmed a 'one size fits all' approach to education is not appropriate in any context. The experiences of the pre-service teachers was divergent due to specific school and factors. Importance of recognising the positive interactions and potential for diverse experiences within a cultural context. Interconnected nature of culture, language and religion and its role in Cook Island schools.